Evaluasi Teknis dan Biaya pada Sistem Penyaliran Tambang di Pit 4 Edward PT Caritas Energi Indonesia Sarolangun Jambi - Nur Annisa; Franto Franto; Delita Ega Andini (MINERAL, 2022)
This research was conducted to redesign the dimensions of the temporary sump to accommodate the total volume of incoming water so as to minimize the occurrence of puddles around the mining area. The method used is a quantitative method by analyzing daily rainfall data for 10 years (2011-2020) using the Gumbell distribution. Actual data in the form of field rainfall intensity, sump water level rise, dimensions and actual discharge of the channel as well as the length and diameter of the pipe. Based on the 5-year return period, the total incoming discharge is 27,043.160 m3/day and based on the maximum rainfall of 30,693.351 m3/day after pumping 607.71 m3/hour for 7 hours, resulting in a residual discharge of 22,789.190 m3/day for 37.5 hours (PUH 5 years) and 26,439.387 m3/day for 43.5 hours (maximum CH). The actual dimensions of all four of Edward's Pit 4 channels are already larger than theoretical. The pump cost which is planned to operate for 7 hours is Rp 408,107.14/day while the actual pump operates 4 hours with additional maintenance costs of Rp 174,811.20/day or ± 42% of the planned cost. Making the actual temporary sump is Rp 73,598,773.90 with an additional cost of making the recommended sump of Rp 62,874,123.60 or ± 85% of the actual cost with a total cost of Rp 272,744,273.